Analysis on the Variation Characteristics of Rainstorm and Cause of Flood in Central Yunnan — Take Downtown of Yuxi City as an Example - ZHU Wenxiang (Renmin Zhujiang)
Taking the downtown of Yuxi as an example,based on the maximum 1h and 24h rainstorm data of Dongfeng station from 1981 to 2019,this paper studies the variation characteristics of short-duration rainstorm in central Yunnan by the linear moving average,Mann-Kendall test and Hurst index,analyzes the causes of urban flood and puts forward countermeasures and suggestions.The results show that:The annual maximum 1 h and 24 h precipitation in downtown of Yuxi presented an insignificant fluctuation and rising trend,with the change rate of 1.4 mm/10a and 0.6 mm/10a respectively.The Hurst index of maximum 1 h and 24 h precipitation over the years is 0.57 and 0.56 respectively,which is consistent with the trend of future changes and relatively weak in continuity.The maximum 1 h precipitation sequence of the Dongfeng station changed suddenly in 1987,2002,2007 and 2013,while the maximum 24 h precipitation sequence changed suddenly in 2000,2009 and 2013.The annual maximum 1 h and 24 h precipitation mostly occurred in August and June,with a high concentration of rainstorm.The average P1h/P24h of the same rainstorm was 47.2%,and the largest proportion was 71.4%.Based on the causes of flood,it is suggested to regulate the river system,improve the pipe network,build new rain and sewage pipe network,construct the sponge city at all areas,and establish a scientific hydrological monitoring system and prediction and early warning platform for urban flood control and drainage.